RHEBL1 expression is activated by the Oct4-Sox2 complex in oral squamous cell carcinoma - Feng Qiu; Yaqiu Chen; Peibo Li; Zhuo Chen; Alfred King-yin Lam; Yuwei Liang; Xiaojing Sun; Qian Jiang; Bin Qiao (Functional & Integrative Genomics, 2026)

Endogenously modified multi-bioresponsive silk fibroin nanoparticles enhancing the cellular delivery and anti-inflammatory activity of curcumin - Sheliang Zhao; Yuwei Sun; Yuxuan Du; Mengjie Yang; Chenxu Gao; Yunshu Ge; Dongning Li; Yang Yang; Xuebo Liu (Food Research International, 2026)

Construction of a three-dimensional visualization system for deep-sea mining plumes based on digital twin technology - Xianming Zhu; Zhicheng Zhang; Zhihan Fan; Enhan Guo; Yuwei Liu; Xinjie Wang; Zhiwen Sun; Yonggang Jia (Marine Georesources & Geotechnology, 2026)

Cyanobacteria relative biomass modulates the contrasting effects of species richness and evenness on phytoplankton resource use efficiency in a mesocosm experiment - Yafang Qin; Chaoyue Cheng; Shangsheng Sun; Ruyi Li; Misha Zhong; Yuwei Wang; Yihan Wang; Zengliang Jian; Chaokun Wang; Yulian Chu; Jianfeng Chen; Haojie Su (Science of The Total Environment, 2026)

Molecular characterization and differential immunomodulatory functions of TGF-β2 and TGF-β3 following Vibrio challenge in Takifugu obscurus - Fenfei Liang; Kun Liu; Xiaorui Zhou; Jinghan Wang; Yufeng Li; Yongqing Sun; Zhaoyang Li; Xin Liu; Yuwei Xu; Yihan Zhang; Guosong Zhang (Fish & Shellfish Immunology, 2026)

Enhanced electron transfer via Fe-Mn synergy in self-nitrogen biochar for rapid and efficient Cr(VI) removal - Yuting Zhang; Li Zhang; Yuwei Tang; Yilong Li; Weibin Sun; Zihao Yang; Jinchunzi Li; Shuang Liang; Jing Zhou (Biomass and Bioenergy, 2026)

Surfactant-enhanced microbial regulation of bituminous coal for improved CO2 adsorption: Interfacial and structural mechanisms - Xin Yi; Hua Gong; Jun Deng; Zujin Bai; Yu Zhang; Yuwei Wang; Wenbin Sun; Shuangyu Tian (Chemical Engineering Journal, 2026)

Deciphering the role of biochar type and particle size in anaerobic co-digestion of food waste and waste activated sludge under thermophilic conditions - Yuwei Yang; Min Zhang; Changhao Zheng; Xiaomei Su; Feng Dong; Xiao Xiao; Liang Xu; Hailu Fu; Faqian Sun (ENGINEERING Environment, 2026)

Unraveling the different roles of enone oxidoreductases (FaEOs) in strawberry to improve aroma quality during cold storage - Pengpeng Sun; Quanzhi Wang; Yuan Ni; Zhiming Yan; Gang Li; Yuanhua Wang; Wei Chen; Qi Zhou; Pengcheng Zhao; Jialong Cheng; Bingxuan Li; Yuwei Tang; et al. (Postharvest Biology and Technology, 2026)

Synergistic catalytic ozonation with an Fe–Mn/AC bimetallic catalyst for enhanced biodegradability and detoxification of pulping wastewater - Can He; Yuwei Sun; Zhongguo Zhang; Xiaofeng Sun; Yue Wu; Yanhui Chen; Liangliang Wang; Jian Zhang; Fengshan Zhang; Hongshun Cheng (Journal of Water Process Engineering, 2026)

Curcumin inhibits colorectal cancer progression by regulating MDH2-mediated glycolysis and NAD+ metabolism - Yuwei Zhao; Hao Qin; Wei Sun; Yu Chen; Ruoyu Wang; Chuang Li (Food and Chemical Toxicology, 2026)

Assessing Regional Resilience of Sub-Saharan Africa Economic Crisis: A Spatial-temporal Analysis Framework Integrating Fisher Information and Multi-scale Geographically Weighted Regression - Ignatius Abasimi; Ye Wei; Yuwei Ma; Xin Sun (Chinese Geographical Science, 2026)

Efficient photocatalytic degradation of neonicotinoid pesticides: Study on properties and mechanism of G-CN modified by cyanocarboxyl - Yiyao Liu; Jian Zhang; Xiaoyue Duan; Yuwei Sun; Xuesong Zhao; Xin Ren (Journal of Water Process Engineering, 2026)

Anisotropic hydrogel with aligned conductive networks enables integrated robustness, high conductivity, and antifouling capability for physiological monitoring - Yu Sun; Yuwei Qiu; Linfa Li; Fanglian Yao; Junjie Li; Xiuqiang Li; Mengyao Zhong; Zhongming Zhao; Ying Zhu; Changyong Wang; Hong Zhang (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Towards the optimization of pulsating ventilation system to improve leaked nitrogen dilution in a factory workshop by SIPC simulation - Chunjie Yu; Yuwei Dai; Wentao Wu; Zhijun Zou; Chanjuan Sun; Haidong Wang (Energy and Buildings, 2026)

Global Warming Amplifies Nitrogen Over Phosphorus Limitation in Aquatic Ecosystems: A Multi‐Trophic Meta‐Analysis - Misha Zhong; Ping Xie; Yuhao Feng; Wenxuan Han; Enzai Du; Di Tian; Ruijing Ma; Yuwei Wang; Zengliang Jian; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; et al. (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) availability fundamentally regulate the structure and function of aquatic ecosystems. While global‐scale patterns of relative nutrient limitation have been increasingly documented, their responses to climate warming remain poorly quantified. To address this, we integrated a global meta‐analysis of nutrient enrichment experiments (spanning 510 sites and multiple trophic levels) with large‐scale datasets of water chemistry from 3403 lakes and 13,032 marine sites. Meta‐analysis showed that primary producers have the strongest responses to nutrient enrichment, especially NP co‐addition, with effects attenuating at higher trophic levels. Increasing temperature amplifies the response of primary producers to nutrient enrichment, but not for consumers, indicating that warming disrupts energy flow to higher trophic levels. Furthermore, relative N limitation of primary producers intensifies with increasing temperature and decreasing latitude in both freshwater and marine ecosystems. Global field observation of water chemistry supports such a pattern as water N:P mass ratios decrease with increasing temperature across lake and marine ecosystems. Our findings provide robust empirical evidence that the relative nutrient limitation of primary producers exhibits a strong latitudinal gradient and climate warming could fundamentally enhance nitrogen over phosphorus limitation in aquatic ecosystems, which have critical implications for ecosystem functioning and management in a warmer world.

Mechanism of PP2A affecting ubiquitination pathway in spermatogenesis - Huamei Ju; Ziliang Geng; Binyan Chen; Yuwei Shang; Xia Chen; Danni Wang; Wenbin Wang; Huiting Sun; Yichao Shi; Jiajun Yu (Reproductive Biology, 2026)

Single-stage bioreactor integrating anammox and sulfur-driven autotrophic denitrification for nitrogen removal from landfill leachate - Liang Xu; Wei Xu; Yuwei Yang; Junwei Wu; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Xiaoxu Zheng; Faqian Sun (Journal of Hazardous Materials, 2026)

Activation of peroxymonosulfate by nickel-cobalt-based PBAs and their derivatives for tetracycline degradation: Degradation mechanism and toxicological evaluation - Wenting Sun; Shiyu Bian; Geng Li; Shuqi Peng; Yuwei Pan; Ming Zhang; Weinan Xing; Xin Huang; Guangyu Wu (Environmental Research, 2026)

Corrigendum to “’Useful’ template synthesis of N-doped acicular hollow porous carbon/carbon-nanotubes for enhanced capture and selectivity of CO2” [Chemical Engineering Journal 361 (2019) 278–285/ WOS:000457096400029] - Xin He; Jing Liu; Yuwei Jiang; Muhammad Yaseen; Haoyu Guan; Jianhua Sun; Xuemin Cui; Dankui Liao; Zhangfa Tong (Chemical Engineering Journal, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Integrating Seasonal-Trend Decomposition and Multi-Head Self-Attention for Feature Fusion with Bidirectional Long Short-Term Memory in Reference Evapotranspiration Prediction - Zehai Gao; Zijun Gao; Chao Sun; Xiaojun Zhang; Siyuan Cao; Yuwei Liu (Water Resources Management, 2026)

Ultrasound-assisted extraction of peptidoglycan from Lactiplantibacillus plantarum: Structural characterization, anti-browning enhancement, and immunomodulatory effects - Yuwei Sun; Kemin Guo; Peiyun He; Dongning Li; Yunshu Ge; Guoqiang Zhang; Xuebo Liu (Food Chemistry, 2026)

Propylparaben induces immunotoxicity in zebrafish via oxidative stress and gut microbiota-immune axis dysregulation - Yong Huang; Jing Hu; Huan Xu; Runhao Zhu; Liting Liu; Xiaomei Chen; Yifan Sun; Yuwei Zhao; Yebing Zhong; Bo Cheng; Xiaochang Huang; Huiqiang Lu; et al. (Fish & Shellfish Immunology, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Insights into the spatiotemporal differences of brown carbon in North China plain: Composition, optical properties and sources - Yuwei Sun; Kehan Sun; Can Wu; Huijun Zhang; Yubao Chen; Zheng Li; Rongjie Li; Binyu Xiao; Yanqin Ren; Gehui Wang (Atmospheric Research, 2026)

Study on mechanical properties of constant-resistance and energy-absorbing bolts for large tunnel deformations - Yuwei Zhang; Jingchao Sun; Zhanping Song; Zhilin Cao; Wei Shi (Tunnelling and Underground Space Technology, 2026)

Mechanisms of blue light-mediated inhibition of chlorophyll degradation in ‘Newhall’ sweet orange during postharvest - Hui Sun; Yuwei Zhou; Sijia Liu; Qianqian Yu; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2026)

Intratracheal perfluorooctane sulfonate induces pulmonary injury via TLRs signaling and disrupts sex steroidogenesis through systemic translocation - Yuwei Chen; Dan Xu; Guanhua Pang; Fanmei Zeng; Yuan Sun; Qing Xia; Luwei Zhao; Yifei Li; Wen Peng; Miao He (Environmental Pollution, 2026)

Watershed boundary extraction from digital elevation models using RBM-SegNet - Huanyu Yang; Hongming Zhang; Yuwei Sun; Lu Du; Weilin Xu; Jincheng Ni; Qiankun Chen; Chunmei Wang; Qinke Yang; Haijing Shi (Environmental Modelling & Software, 2026)

Electronic bridge construction at plasmonic heterointerfaces for highly selective CO2 photoreduction to CH4 - Ming Sun; Yuwei Tan; Kai Wang; Xiaoli Zhao; Jiacheng Wang; Peng Chen; Ming Huang (Chemical Engineering Journal, 2026)

Anion-induced hydrogen-bonded organic frameworks with highly efficient solid-state white-light emission - Qilong Zhang; Xu Zhou; Yuxin Xie; Yuwei Bao; Xiaofeng Shan; Tao Sun; Lingyi Shen; Zhiyong Wang; Hong Xu; Carl Redshaw; Xing Feng (Chemical Engineering Journal, 2026)

Hierarchical-doping conducting polymer-based hydrogel for photothermal-activated microenvironment remodeling in myocardial infarction - Yuwei Qiu; Chaojie Yu; Xiaobo Xu; Xiaochen Lu; Fanglian Yao; Hong Sun; Hong Zhang; Junjie Li (Chemical Engineering Journal, 2026)

GPU-accelerated Krylov subspace methods for fast fluid dynamics simulation of indoor/outdoor airflow - Lei Cheng; Yuwei Dai; Wentao Wu; Zhijun Zou; Chanjuan Sun; Haidong Wang (Building and Environment, 2026)

Algae-microplastics interactions and their significance in combating aquatic plastic pollution - Wensi Zhao; Yuwei Sun; Chengyu Suo; Jingru Zhang; Huanliang Lu; Xuesong Liu; Hailei Su; Fanfan Wang; Ningning Ji; Min Zhou; Fengchang Wu; Yuan Wei (ENGINEERING Environment, 2026)

Image-based modelling of attachment density and morphometric size in Rhopilema esculentum polyps - Fudi Chen; Yan Duan; Yuwei Zhang; Yuhao Xian; Qiyang Min; Ming Sun (Frontiers in Marine Science, 2025)
Accurate monitoring of polyp attachment density is critical for the efficient culture of the edible jellyfish Rhopilema esculentum , yet quantitative density–growth guidelines remain limited. This study coupled image-based deep learning with conventional morphometry to characterise density-dependent growth of polyps. Polyp calyx diameter was measured manually to establish a density–size relationship. In parallel, standardised photography combined with a U-Net segmentation model was used to obtain individual polyp counts and projected areas. Regression analyses were conducted to derive functional relationships between attachment density and polyp size metrics, and processing times were compared between manual and automated approaches. Manual measurements showed that calyx diameter followed a power-law decay with density ( Calyx diameter = 1.5752Density -0.281 , R 2 = 0.9614). Automated image analysis yielded an exponential density–polyp area model ( Polyp area = 4.3888e -0.202 Density , R 2 = 0.9909). Both models revealed a strong inverse relationship: as attachment density increased, average polyp size and relative growth efficiency declined, whereas size variability increased. The U-Net-based segmentation approach achieved processing times of under one second per image, dramatically faster than manual measurements. These results demonstrate that AI-driven image segmentation provides accurate, high-throughput estimation of polyp size and robust quantitative density–growth relationships. The approach offers a practical and efficient tool for precision monitoring and optimisation of nursery conditions in R. esculentum aquaculture.

Tree trunk disease mapping using hyperspectral LiDAR - Peilun Hu; Yuwei Chen; Wei Li; Huaguo Huang; Samuli Junttila; Shuanghui He; Yanan Zhao; Xiaoqi Cui; Mohammad Imangholiloo; Changhui Jiang; Jianxin Jia; Haibin Sun; et al. (Computers and Electronics in Agriculture, 2025)

Promoting electron transfer and increasing oxygen vacancies on Cu-doped Co3O4 for enhanced peroxomonosulfate activation for tetracycline removal - Yin Zhu; Qian Tang; Kai Wu; Zhikai Zhang; Yuwei Sun; Wei Jiang; Yonghui Gao (Journal of Environmental Chemical Engineering, 2025)

Liquid-like PDMS brushes/TiO2 microcapsule-driven coatings with integrated self-healing, photodegradation, and antifouling functions - Jingjing Ren; Taolin Zhang; Shouzheng Jiao; Fanghua Pan; Jingru Sun; Ran Mo; Yuwei Hao; Zhengyu Chen; Siqiao Zhang; Zhicheng Sun; Zhongjun Cheng (Journal of Environmental Chemical Engineering, 2025)

Atomic-scale regulation of Bi2Te3 nanopores via in-situ electron beam irradiation for nanofabrication - Yuting Shen; Yu Tao; Tao Xu; Yuwei Xiong; Kuibo Yin; Yilong Zhou; Shan Cong; Litao Sun (Chemical Engineering Journal, 2025)

Zn-MOF derived from waste plastic bottles activated peroxymonosulfate for the degradation of oxytetracycline: Process mechanism and toxicological analysis - Shiyu Bian; Wenting Sun; Yuwei Pan; Ming Zhang; Guangyu Wu; Yudong Huang (Chemical Engineering Journal, 2025)

Butterfly-inspired ultraviolet vision chip based on ZnO memristor arrays for real-time dynamic plant motion tracking - Yang Liu; Junmeng Guo; Jiao Wang; Yuwei Zhao; Yatao Zhang; Guangxiang Gu; Haoran Ruan; Pengfei Li; Yu Sun; Luyao Zhang; Zuliang Du; Gang Cheng (Chemical Engineering Journal, 2025)

High-intensity fish disturbance reduces ecosystem multifunctionality by diminishing planktonic bacterial diversity and network complexity - Shangsheng Sun; Jianfeng Chen; Qingyang Rao; Yuwei Wang; Ruyi Li; Misha Zhong; Yihan Wang; Zengliang Jian; Chaokun Wang; Yafang Qin; Yulian Chu; Ping Xie; et al. (Biological Conservation, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Freezing-Activated Oxidation with Nitrite and H2O2 for Efficient Waste Activated Sludge Solubilization and Filterability - Min Zhang; Yuwei Yang; Xiaomei Su; Faqian Sun; Jianbo Liu; Yun Chen; Dan Lu; Feng Dong; Xiao Xiao; Yan Zhou (Water Research, 2025)

Source-specific insights into photochemical and microbial degradation of dissolved organic matter in coastal environments - Bin Wang; Xuelu Gao; Simon F. Thrush; Yongliang Liu; Xiyan Sun; Jianmin Zhao; Qianguo Xing; Yuwei Yang (Marine Environmental Research, 2025)

Hierarchical Janus sponge evaporator functionalized with liquid-like PDMS molecular brushes for efficient and sustainable solar evaporation and electricity generation - Siying Guan; Taolin Zhang; Shouzheng Jiao; Rongxue Xi; Rui Ma; Chenshun Hu; Yuwei Hao; Zhicheng Sun; Zhongjun Cheng (Chemical Engineering Journal, 2025)

Analysis of the confounding factors of PM2.5-bound polycyclic aromatic hydrocarbons in population exposure in Xi’an City, China - Min Gao; Jieting Zhou; Xiaoxia Sun; Yang Yang; Yuwei Li; Hongmei Xu (Air Quality, Atmosphere & Health, 2025)

Integrative scATAC-seq and mtDNA mutation analysis reveals disease-driven regulatory aberrations in AML - Chen Tian; Yijun Dong; Xin Sun; Longchen Xu; Xiaoli Ma; Yuwei Tao; Fang Wang; Haohang Zhang; Jie Li; Kun Li; Yasong Chen; Hongxing Liu; et al. (Science Bulletin, 2025)

Resource utilization of saturated adsorbed phosphate removal materials: material reuse, recovery of phosphate, and resource utilization of iron and aluminum - Xiangjun Sun; Mazhan Zhuang; Liang Zhang; Yuwei Deng; Wei Cao; Fei Li; Zhenming Zhou; Denghong Wang (Journal of Water Process Engineering, 2025)

Utilization of waste iron sludge to achieve bifunctional magnetic and adsorptive cores for synthesizing magnetic chitosan microspheres: Arsenic decontamination and its mechanism - Weihua Zhao; Huiping Zeng; Qihan Wang; Xiao Sun; Yuwei Zeng; Dong Li; Jie Zhang (Process Safety and Environmental Protection, 2025)

An injectable hydrogel with oxygen-generating and antioxidant properties for cardiac repair - Haitao Zhang; Lei Liang; Yuwei Qiu; Xin Sun; Zhiwei Yue; Yue Wang; Ning Ma; Hong Zhang; Fanglian Yao; Jin Zhou; Hong Sun; Junjie Li (Chemical Engineering Journal, 2025)

Antimony and arsenic interactions with iron oxides and aluminum oxides in surface environment: A review focused on processes and mechanisms - Shuo Xiang; Zhiyou Fu; Hongyue Lu; Yuwei Sun; Yimeng Shen; Fengchang Wu (Science of The Total Environment, 2025)

Sulfide-modified zero-valent iron enhanced activation of sodium bromate for sulfamethoxazole removal: Sulfur species and multiple reactive species role - Minyi Yu; Yajing Mao; Shang Gao; Xinjie Jiang; Yao Duan; Xiaoyu Li; Xiang Li; Haiyang Sun; Ying Zhang; Yuwei Pan (Journal of Environmental Chemical Engineering, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Assessing indoor radon concentration: Field study from a university campus in Shanghai - Xionghui Ma; Chunxiao Su; Ziyi Zhu; Zhijun Zou; Yuwei Dai; Chanjuan Sun; Haidong Wang (Building and Environment, 2025)

Preserving aroma in east and southeast Asian sauces: A review of thermal and non-thermal processing techniques - Shouqingyun Sun; Yihao Yin; Yuwei Xiang; Zibo Song; Ming Du; Chaofan Guo; Junjie Yi (Innovative Food Science & Emerging Technologies, 2025)

Heterostructural Cu2S@CuO nanoarrays enable peroxymonosulfate activation for sulfamethoxazole degradation through non-free radical pathways - Lei Shi; Yuwei Li; Hao Dong; Jin Sun; Changlei Xia; Liping Cai; Bin Hui (Desalination, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

A dual chiral porous organic polymer synthesized by thiol-yne click chemistry strategy for capillary gas chromatography separations - Wei Wang; Jiangjiang Zhang; Zhen Wang; Yuwei Wang; Liquan Sun; Yukui Zhang; Aiqin Luo (Analytica Chimica Acta, 2025)

Recent advances and potentiality of phenyllactic acid: Source, antimicrobial mechanism, and applications - Yuwei Sun; Jiang Zhu; Tao Wang; Zhijia Liu; Chuanqi Chu; Junjie Yi (Trends in Food Science & Technology, 2025)

Regulation of the colloidal organic matter in coastal waters by scallop farming - Bin Wang; Xuelu Gao; Liming Wang; Xiaoxiao Yu; Yongliang Liu; Xiyan Sun; Jianmin Zhao; Qianguo Xing; Yuwei Yang (Marine Environmental Research, 2025)

Flood risk in mountainous settlements: A new framework based on an interpretable NSGA-II-GB from a point-area duality perspective - Qijiang Wu; Zhe Sun; Zhan Wang; Lu Zheng; Jiaxing Jiang; ZiLan Zhong; Yuwei Jia (Journal of Environmental Management, 2025)

Lignosulfonate modified zero-valent iron enhanced activation of peroxymonosulfate for sulfamethazine removal: Performance and mechanism - Yao Duan; Xiaoyu Li; Shang Gao; Minyi Yu; Lichun Fu; Ying Zhang; Haiyang Sun; Yuwei Pan (Chemical Engineering Journal, 2025)

Down-regulation of miR-138-5p in PP2A KO mice promoted apoptosis of spermatocytes - Danni Wang; Xing Liu; Bingyan Chen; Yuwei Shang; Ting Wan; Shu Zhang; Huijun Liu; Yichao Shi; Xia Chen; Huiting Sun (Molecular Biology Reports, 2024)

Constructing 3D SPAD distribution using hyperspectral LiDAR point cloud by PROSPECT model inversion - Hui Shao; Dingrun Liu; Yuwei Chen; Long Sun; Huiming Wang; Cheng Wang; Bin Zhu; Yuxia Hu (International Journal of Remote Sensing, 2024)

Optimization of operational parameters of marine methanol dual-fuel engine based on RSM-MOPSO - Junshuai Lv; Yuwei Sun; Zhiqing Zhang; Yunhu Fang (Process Safety and Environmental Protection, 2024)

Scallop farming impacts on dissolved organic matter cycling in coastal waters: Regulation of the low molecular weight fraction - Bin Wang; Xuelu Gao; Yongliang Liu; Xiyan Sun; Jianmin Zhao; Qianguo Xing; Yuwei Yang (Marine Environmental Research, 2024)

Cyclic di-GMP incorporates the transcriptional factor FleQ03 in Pseudomonas syringae MB03 to elicit biofilm-dependent resistance in response to Caenorhabditis elegans predation - Xiaowen Sun; Fan Xiao; Yuwei Su; Zhi Li; Xun Yu; Rebecca E. Parales; Lin Li (Journal of Invertebrate Pathology, 2024)

Numerical investigation on dynamic flow characteristics of methane condensation in microchannels - Yuwei Sun; Cong Zhao; Haocheng Wang; Yinan Qiu; Maoqiong Gong; Yanxing Zhao (International Journal of Refrigeration, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Research progress and prospect of covalent organic frameworks (COFs) and composites: From synthesis to application in water contaminants - Rui Li; Fengfei Sun; Zhen Liu; Yuwei Shi; Sizhe He; Junfeng Chen (Journal of Environmental Chemical Engineering, 2024)

Numerical studies on the effects of the hybrid cooling and dust suppression solution in hot fully-mechanized mining face - Song Xin; Xuefei Han; Qifei Sun; Menglin Li; Yuwei Wu; Zhen Zhang; Wenyu Yang (International Journal of Refrigeration, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

SnO2 induced electrostatic polarization PVDF composite nanofibers for efficient energy harvesting and self-powered wireless monitoring /motion recognition systems - Bozhi Wu; Yongqiang Yang; Lei Wang; Hui Xu; Yuheng Huang; Jiahong Kang; Yuwei Xiong; Kuibo Yin; Meng Nie; Litao Sun (Chemical Engineering Journal, 2024)

Technological readiness of commercial microalgae species for foods - Shufang Yang; Yuwei Fan; Yue Cao; Yuxin Wang; Haijin Mou; Han Sun (Critical Reviews in Food Science and Nutrition, 2024)

Ocean water colour retrieval method based on directional polarimetric camera - Yuwei Pan; Jingjing Chen; Feinan Chen; Guangfeng Xiang; Donggen Luo; Liang Sun; Jin Hong; Shuangbao Shu (International Journal of Remote Sensing, 2024)

Integrated transcriptomic and metabolomic analyses revealed the effect of melatonin on delaying persimmon fruit softening - Yuwei Wang; Shiyu Lin; Mengyuan Zhang; Jiaojiao Nie; Aijun Tang; Ningjing Sun; Shuyu Zeng; Xiaofen Liu; Yuduan Ding; Xueren Yin; Qinggang Zhu (Postharvest Biology and Technology, 2024)

Metal exposure and blood lipid biomarkers in early pregnancy: A cross-sectional study - Rui Yang; Fengjiang Sun; Xiong-Fei Pan; Yingqian Su; Ping Wu; Jiaying Yuan; Yuwei Lai; An Pan; Wei Huang (Environmental Pollution, 2024)

The overall stability of a partially unstable reservoir bank slope to water fluctuation and rainfall based on Bayesian theory - Wengang Zhang; Songlin Liu; Luqi Wang; Weixing Sun; Yuwei He; Yankun Wang; Guanhua Sun (Landslides, 2024)

Enhanced reduction of graphene oxide via laser-dispersion coupling: Towards large-scale, low-defect graphene for crease-free heat-dissipating membranes in advanced flexible electronics - Jiawei Sun; Yuwei Xiong; Haiyang Jia; Longxiang Han; Wen Ye; Litao Sun (Science Bulletin, 2024)

Boosting peroxymonosulfate activation with a composite of highly dispersed FeS2 nanoparticles anchored on N-doped biochar for efficient tetracycline degradation - Wenqi Bao; Qian Tang; Yixin Fan; Yin Zhu; Yonghui Gao; Yuwei Sun; Hao Liu (Journal of Environmental Chemical Engineering, 2024)

Flow boiling heat transfer characteristics and correlation development of R290/R600a mixtures in an internally threaded tube - Cong Zhao; Yuwei Sun; Hao Guo; Yanxing Zhao; Maoqiong Gong; Zhiqiang Yang (International Journal of Refrigeration, 2024)

Investigations on the heat transfer enhancement of converging minitubes for methane condensation - Yuwei Sun; Haocheng Wang; Feng Nie; Maoqiong Gong; Jun Shen (International Journal of Refrigeration, 2024)

Exploring T7 RNA polymerase-assisted CRISPR/Cas13a amplification for the detection of BNP via electrochemiluminescence sensing platform - Zaiyong Zhang; Jinglong Li; Chunlin Chen; Yuwei Tong; Dehui Liu; Cuizhi Li; Huan Lu; Li Huang; Wanling Feng; Xiaoting Sun (Analytica Chimica Acta, 2024)

Feasibility study of forest wood-boring pest detection base on hyperspectral LiDAR - Hui Shao; Hulong Zhang; Peilun Hu; Yuwei Chen; Wei Li; Long Sun; Yuxia Hu (International Journal of Remote Sensing, 2024)

Day-ahead optimal scheduling of hydropower-dominated power grids under a spot market environment - Wenlin Yuan; Yingyi Sun; Chengguo Su; Yang Wu; Hangtian Guo; Yuwei Tang (Journal of Cleaner Production, 2024)

The emerging roles of next-generation metabolomics in critical care nutrition - Kefeng Li; Henry Hoi Yee Tong; Yuwei Chen; Yizhu Sun; Jing Wang (Critical Reviews in Food Science and Nutrition, 2024)

Single-cell transcriptomics reveals the pulmonary inflammation induced by inhalation of subway fine particles - Weilai Zhou; Wenke Yuan; Yuwei Chen; Chao Li; Liwen Hu; Qidian Li; Jiawei Wang; Rou Xue; Yuan Sun; Qing Xia; Longji Hu; Yuan Wei; et al. (Journal of Hazardous Materials, 2024)

Combined pollution characteristics and ecological risks of multi-pollutants in Poyang Lake - Hongyue Lu; Zhiyou Fu; Yujun Tong; Shuo Xiang; Yuwei Sun; Fengchang Wu (Environmental Pollution, 2024)

Increased fine root production coupled with reduced aboveground production of plantations under a three-year experimental drought - Cuiting Wang; Yuan Sun; Xiaoming Zou; Han Y.H. Chen; Manuel Delgado-Baquerizo; Jingyan Yang; Guobing Wang; Yuwei Liu; Honghua Ruan (Science of The Total Environment, 2024)

Facile preparation of maghemite based on iron sludge for arsenic removal from water - Huiping Zeng; Weihua Zhao; Siqi Sun; Xiao Sun; Yuwei Zeng; Ruixia Hao; Jie Zhang; Dong Li (Science of The Total Environment, 2024)

Superb microplastics separation performance of graphene oxide tuned by laser bombardment - Jiawei Sun; Yuwei Xiong; Haiyang Jia; Longxiang Han; Kuibo Yin (Journal of Hazardous Materials, 2024)

Role of sulfate in regulating performance and metabolic mechanisms of bioelectrochemical up-flow anaerobic sludge blanket fed with methanolic wastewater - Yijing Gao; Bin Chen; Wanjiang Li; Yule Han; Zhaobin Liu; Yuwei Sun; Guihua Zhuo; Xueqin Lu; Samir Ibrahim Gadow; Weijie Hu; Guangyin Zhen (Journal of Cleaner Production, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Water use strategy of nitraria tangutorum shrubs in ecological water delivery area of the lower inland river: Based on stable isotope data - Dongdong Qiu; Guofeng Zhu; Mohd Aadil Bhat; Lei Wang; Yuwei Liu; Liyuan Sang; Xinrui Lin; Wenhao Zhang; Niu Sun (Journal of Hydrology, 2023)

Heavy metals immobilization of ternary geopolymer based on nickel slag, lithium slag and metakaolin - Jinyuan Fan; Jiahao Yan; Mengya Zhou; Yuan Xu; Yuwei Lu; Ping Duan; Yingcan Zhu; Zuhua Zhang; Wengui Li; Aiguo Wang; Daosheng Sun (Journal of Hazardous Materials, 2023)

A comparison between Pixel-based deep learning and Object-based image analysis (OBIA) for individual detection of cabbage plants based on UAV Visible-light images - Zhangxi Ye; Kaile Yang; Yuwei Lin; Shijie Guo; Yiming Sun; Xunlong Chen; Riwen Lai; Houxi Zhang (Computers and Electronics in Agriculture, 2023)

Inhalation of subway fine particles induces murine extrapulmonary organs damage - Jiawei Wang; Rou Xue; Chao Li; Liwen Hu; Qidian Li; Yuan Sun; Yuwei Chen; Wenke Yuan; Qing Xia; Longji Hu; Yuan Wei; Miao He (Science of The Total Environment, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Incidence and Risk Factors for Dysphagia Following Cerebellar Stroke: a Retrospective Cohort Study - Li Huang; Yunlu Wang; Jikang Sun; Lequn Zhu; Jimin Liu; Yuwei Wu; Chunlei Shan; Juntao Yan; Ping Wan (The Cerebellum, 2023)
The cerebellum is known to play a supportive role in swallowing-related functions; however, wide discrepancies about the incidence rate of swallowing disorders following cerebellar strokes exist within the literature. This study aimed to investigate the incidence rate of dysphagia and the factors which may affect the presence of dysphagia and clinical recovery in individuals diagnosed with cerebellar stroke. A retrospective chart audit of 1651 post-stroke patients (1049 males and 602 females) admitted with a cerebellar stroke to a comprehensive tertiary hospital in China was conducted. Data on demographics, medical, along with swallowing function assessment were collected. Differences between dysphagic and non-dysphagic groups were evaluated using t -tests and Pearson’s chi-square test. Univariate logistic regression analysis was performed to establish factors associated with the presence of dysphagia. A total of 11.45% of participants were identified with dysphagia during inpatient admission. Individuals with mixed types of stroke, multiple lesions in the cerebellum, and ages older than 85 years old were more likely to develop dysphagia. Moreover, the prognosis of dysphagia following a cerebellar stroke was associated with lesions in different parts of the cerebellum. The cumulative recovery rates from the best to worse were the right hemisphere group, the cerebellum vermis or peduncle group, and both the hemisphere group and the left hemisphere group, respectively.

Intratracheally administered iron oxide nanoparticles induced murine lung inflammation depending on T cells and B cells - Yuan Sun; Yuwei Chen; Jiawei Wang; Wenke Yuan; Rou Xue; Chao Li; Qing Xia; Longji Hu; Yuan Wei; Miao He; Kefang Lai (Food and Chemical Toxicology, 2023)

A review of additives use in straw composting - Mingyue Piao; Ang Li; Huishi Du; Yuwei Sun; Hongxue Du; Honghui Teng (Environmental Science and Pollution Research, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Evaluation of Chinese populational exposure to environmental electromagnetic field based on stochastic dosimetry and parametric human modelling - Yuwei Jiang; Hongkai Wang; Xiaobang Sun; Congsheng Li; Tongning Wu (Environmental Science and Pollution Research, 2023)

The use of stable isotopes to determine optimal application of irrigation-water to a maize crop - Lei Wang; Guofeng Zhu; Dongdong Qiu; Yuwei Liu; Kailiang Zhao; Liyuan Sang; Zhuanxia Zhang; Zhigang Sun; Leilei Yong; Yinying Jiao (Plant and Soil, 2023)

Inheritance and Development: The Evolution and Overview of China’s Fisheries Legal System - Wei Wu; Yang Liu; Zhaobin Pei; Yan Lin; Xin Sun; Jiaqi Xing; Yuwei Wang; Yu Liu (Fishes, 2022)
China’s legal system governing fisheries in China has been stable during development. In line with China’s national conditions and the spirit of the times, they have adhered to the concept of green development and maintaining the sustainable development of fishery production activities. Studying the history of Chinese fishery law is beneficial for the world to understand the evolution of this legislation and is a better gateway for the world to understand fisheries law with Chinese characteristics. Fishery, in this context, refers to fishing and fish farming. In China, fisheries are under the management of the Ministry of Agriculture and Rural Affairs, while fisheries enforcement has a special law enforcement department for collaborative management. Therefore, both fishing and fish farming in China’s fisheries industry belong to the category of agriculture. This is different from the West and is precisely what makes China unique. This paper explores the Chinese fishery legal and general legal systems by investigating policy guidelines, laws, and regulations on China’s fishery industry since 1949. Furthermore, it analyzes the development process of fisheries. Organizing the development status of China’s fishery legal and regulatory system analyzes the problems of fishery production control and development, searches for paths and methods to solve the practical problems, and finally, makes a reasonable outlook on the development prospect of China’s fishery.

N-doped graphene aerogel cathode with internal aeration for enhanced degradation of p-nitrophenol by electro-Fenton process - Qian Tang; Sijia Luo; Hang Gao; Yixin Fan; Wenqi Bao; Yonghui Gao; Yuwei Sun; Chunwei Yang (Environmental Science and Pollution Research, 2022)

Open-source optimization method for android smartphone single point positioning - Changhui Jiang; Yuwei Chen; Jianxin Jia; Haibin Sun; Tinghuai Wang; Zhiyong Duan; Juha Hyyppa (GPS Solutions, 2022)
Nowadays, a chip-scale Global Navigation Satellite System (GNSS) receiver is ubiquitous in smartphones. In a smartphone GNSS receiver, the least square (LS) or Kalman Filter (KF) is implemented to estimate the position. With the aim to improve the smartphone GNSS position accuracy, we propose a position-smoothing method considering more historical information than the traditional methods, i.e., LS and KF. More past states are regarded as unknowns, and a cost function is constructed to optimize these states. An open-source smartphone dataset from Google was used for testing the proposed method. The experimental results indicate that the proposed method outperforms the other conventional methods in position errors. In addition, we open the source code. We expect that the optimization method implemented in the smartphone GNSS position smoothing application can be an illustrative example to clearly introduce such an optimization method and a reference for its implementation, which might inspire some other meaningful and exciting applications in GNSS.

Implementation and performance analysis of the PDR/GNSS integration on a smartphone - Changhui Jiang; Yuwei Chen; Chen Chen; Jianxin Jia; Haibin Sun; Tinghuai Wang; Juha Hyyppa (GPS Solutions, 2022)
Pedestrian dead reckoning (PDR) is an effective technology for pedestrian navigation. In PDR, the steps are detected with the measurements of self-contained sensors, such as accelerometers, and the position is updated with additional heading angles. A smartphone is usually equipped with a low-cost microelectromechanical system accelerometer, which can be utilized to implement PDR for pedestrian navigation. Since the PDR position errors diverge with the walking distance, the global navigation satellite system (GNSS) is usually integrated with PDR for more reliable position results. This paper implemented a smartphone PDR/GNSS via a Kalman filter and factor graph optimization (FGO). In the FGO, the PDR factor is modeled, and the states are correlated with a dead reckoning algorithm. The GNSS position is modeled as the “GNSS” factor to constrain the states at each step. With a graphic model representing the states and measurements, the state estimation is converted to a nonlinear least square problem, and we utilize the Georgia Tech Smoothing and Mapping graph optimization library to implement the optimization. We tested the proposed method on a Huawei Mate 40 Pro handset with a standard playground field test, and the field test results showed that the FGO effectively improved the smartphone position accuracy. We have released the source codes and hope that they will inspire other works on pedestrian navigation, i.e., constructing an adaptive multi-sensor integration system using FGO on a smartphone.

Self-regeneration hybrid hydrogel for bisphenol a adsorption in water - Mingyue Piao; Hongxue Du; Yuwei Sun; Honghui Teng (Environmental Science and Pollution Research, 2022)

Integrating UPLC-QE-Orbitrap-MS technology and network pharmacological method to reveal the mechanism of Bailemian capsule to relieve insomnia - Hao Wu; Yijia Cao; Yuxia Qu; Tianyi Li; Jiaqi Wang; Yuwei Yang; Chenning Zhang; Yikun Sun (Natural Product Research, 2022)

Electrocoagulation pretreatment of pulp and paper wastewater for low pressure reverse osmosis membrane fouling control - Chenhao Gong; Xiaojing Ren; Zhongguo Zhang; Yuwei Sun; Haiou Huang (Environmental Science and Pollution Research, 2022)

The geochemical behavior of trace metals and nutrients in submerged sediments of the Three Gorges Reservoir and a critical review on risk assessment methods - Bin Wang; Shu Chen; Yuwei Chen; Nelson Belzile; Rui Zheng; Yuankun Yang; Kaibin Fu; Yongcan Chen; Binliang Lin; Zhaowei Liu; Jian Sun (Environmental Science and Pollution Research, 2021)

Distribution, sources, and ecological risk assessment of polycyclic aromatic hydrocarbons in the sediments of Daihai Lake in Inner Mongolia, China - Yuwei Sun; Ruiqing Zhang; Ruipeng Ma; Haijun Zhou; Fujin Zhang; Guanghui Guo; Huixian Li; Changwei Lü (Environmental Science and Pollution Research, 2021)

Correction to: Shuangxia decoction alleviates p-chlorophenylalanine induced insomnia through the modification of serotonergic and immune system - Yujie Sun; Wenhui Pei; Na Zhang; Yuxia Qu; Yijia Cao; Jianhao Li; Yuwei Yang; Tiange Yang; Fang Fang; Yikun Sun (Metabolic Brain Disease, 2020)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Synthesis of char-based adsorbents from cotton textile waste assisted by iron salts at low pyrolysis temperature for Cr(VI) removal - Zhihua Xu; Siyi Gu; Zhenhua Sun; Daofang Zhang; Yuwei Zhou; Yuquan Gao; Renzhi Qi; Weifang Chen (Environmental Science and Pollution Research, 2020)

Shuangxia decoction alleviates p-chlorophenylalanine induced insomnia through the modification of serotonergic and immune system - Yujie Sun; Na Zhang; Yuxia Qu; Yijia Cao; Jianhao Li; Yuwei Yang; Tiange Yang; Yikun Sun (Metabolic Brain Disease, 2020)

Modulation of Beta Oscillations for Implicit Motor Timing in Primate Sensorimotor Cortex during Movement Preparation - Hongji Sun; Xuan Ma; Liya Tang; Jiuqi Han; Yuwei Zhao; Xuejiao Xu; Lubin Wang; Peng Zhang; Luyao Chen; Jin Zhou; Changyong Wang (Neuroscience Bulletin, 2019)

Effects of different scrap iron as anode in Fe-C micro-electrolysis system for textile wastewater degradation - Zhenhua Sun; Zhihua Xu; Yuwei Zhou; Daofang Zhang; Weifang Chen (Environmental Science and Pollution Research, 2019)

PB2 and hemagglutinin mutations confer a virulent phenotype on an H1N2 avian influenza virus in mice - Zhijun Yu; Zhiguang Ren; Yongkun Zhao; Kaihui Cheng; Weiyang Sun; Xinghai Zhang; Jiaqiang Wu; Hongbin He; Xianzhu Xia; Yuwei Gao (Archives of Virology, 2019)

Forecasting CO2 emissions in Hebei, China, through moth-flame optimization based on the random forest and extreme learning machine - Sun Wei; Wang Yuwei; Zhang Chongchong (Environmental Science and Pollution Research, 2018)

Fluorescent Carbon Dots as Cost-Effective and Facile Probes for Caffeic Acid Sensing via a Fluorescence Quenching Process - Qianqian Sun; Yuwei Long; Hongxi Li; Shuang Pan; Jidong Yang; Shaopu Liu; Xiaoli Hu (Journal of Fluorescence, 2018)

Mutations of key driver genes in colorectal cancer progression and metastasis - Dongdong Huang; Wenjie Sun; Yuwei Zhou; Peiwei Li; Fang Chen; Hanwen Chen; Dajing Xia; Enping Xu; Maode Lai; Yihua Wu; Honghe Zhang (Cancer and Metastasis Reviews, 2018)

PB2 and HA mutations increase the virulence of highly pathogenic H5N5 clade 2.3.4.4 avian influenza virus in mice - Zhijun Yu; Kaihui Cheng; Weiyang Sun; Xinghai Zhang; Xianzhu Xia; Yuwei Gao (Archives of Virology, 2018)

Recombination between DEP1 and NRT1.1B under japonica and indica genetic backgrounds to improve grain yield in rice - Mingzhu Zhao; Xin Geng; Wenjing Bi; Quan Xu; Jian Sun; Yuwei Huang; Qingying Wang; Wenjing Zheng; Zhengjin Xu (Euphytica, 2017)

RNA binding protein QKI contributes to WT1 mRNA and suppresses apoptosis in ST cells - Xin Liu; Jia Guo; Mengjiao Zhou; Yuwei Yang; Mengdi Liang; Chunyan Bai; Zhihui Zhao; Boxing Sun (Genes & Genomics, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Genetic characterization of an isolate of canine distemper virus from a Tibetan Mastiff in China - Weike Li; Tiansong Li; Yuxiu Liu; Yuwei Gao; Songtao Yang; Na Feng; Heting Sun; Shengle Wang; Lei Wang; Zhigao Bu; Xianzhu Xia (Virus Genes, 2014)

Experimental study on dynamic properties and constitutive model of polypropylene fibre concrete under high-strain rates - Hua Zhang; Yuwei Gao; Fei Li; Feng Lu; Hao Sun (European Journal of Environmental and Civil Engineering, 2013)

Mechanism of attenuation coefficient variability of underwater upward radiance - Qiaohua Zhao; Chunhua Ji; Deyong Sun; Hui Zhang; Yuwei Jiang; Rongyin Tao; Haozhong Qian (International Journal of Remote Sensing, 2013)

Comparison of Greenhouse and Field Degradation Behaviour of Isoprocarb, Hexaflumuron and Difenoconazole in Perilla frutescens - Caixia Sun; Hu Zhang; Tao Tang; Mingrong Qian; Yuwei Yuan; Zhiheng Zhang (Bulletin of Environmental Contamination and Toxicology, 2012)